Aggressiveness of Belarussian Polessie Ground Water - G. A. Kolpashnikov; R. I. Lenkevich (Наука и техника)
The paper contains results of the investigations in respect of the aggressiveness of ground water within the area of Belarussian Polessie. Four zones of its spreading have been located and impact of the melioration on formation of aggressive water has been analyzed.